Analisis pajak kendaraan bermotor di Unit Pelaksana Teknis Daerah Kabupaten Minahasa Utara - Pelealu, Revelino Imanuel; Ilat, Ventje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2019)
Motorized vehicle are all wheeled vehicles, along with the trailer used in all type of road, and are driven by technical equipment in the form of a motor or commonly called a machine. Motor Vehicle Tax is one of the potential sectors in increasing Original Regional Income in North Minahasa Regency. The purpose of this study is to analyze the constraints or problems of 2015-2018 Motor Vehicle Tax that have fluctuated. This research was conducted at the Regional Technical Implementation Unit of North Minahasa Regency. The data analysis method used is qualitative descriptive method. The results of the study found that vehicle tax in 2015 did not reach the target, with the realization of the revenue amounting to Rp 49.696.733.900 from the target set at Rp 57.601.380.834 while 2016 to 2018 reached the target. The natural obstacle at the time was that the Data Base from DISPENDA had not been integrated with the North Sulawesi Police Department. The conclusion is that the realization of the target in the last 4 years is not achieved, namely in 2105 and the rest has increased.